PENGARUH KOMPETENSI, POLA KARIR DAN FUNGSI AUDITOR TERHADAP SERTIFIKASI PENJENJANGAN JABATAN FUNGSIONAL AUDITOR PADA KANTOR INSPEKTORAT KABUPATEN PINRANG - Rahma, Rika (Universitas Muhammadiyah Parepare, 2018)
The Influence of Competence, Career Patterns, and Auditor Functions on Certification of Auditor Functional Auditor Functional at Inspectorate Office of Pinrang Regency. (Supervised By Mursalim and Muhammad Su'un) This study aims to: to know the Influence generated competence, career pattern and function of auditor toward certification functional functional Auditor gap at Inspectorate Office of Pinrang Regency. This Research Type is Quantitative Research. The object of this research is Inspectorate Office of Pinrang Regency. Sampling technique using census method. Data collection conducted using questionnaires distributed directly to the existing employees at the Inspectorate Office of Pinrang Regency.The results of this study indicate that (1) Competence positively and positively affect the Certification of Functional Auditor Functional Auditor. (2) Career Pattern has negative and insignificant effect on Certification of Functional Auditor Functional Auditor. (3) Auditor function has positive and insignificant effect on Certification of Auditor Functional Auditor Function.